2018
DOI: 10.1080/17453674.2018.1530173
|View full text |Cite
|
Sign up to set email alerts
|

Nonagenarians qualify for total knee arthroplasty: a report on 329 patients from the Swedish Knee Arthroplasty Register 2000–2016

Abstract: Background and purpose — The nonagenarian (those aged 90 years and older) population is expected to double in the next 20 years. This demographic age quake may have a significant impact on the incidence of total knee arthroplasty (TKA), although current literature provides limited data. We examined death and revision rates, patient-reported outcomes (PROs) and bias on patient selection of nonagenarian patients operated on with TKA for osteoarthritis (OA) between 2000 and 2016.Patients and methods — The Swedish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 26 publications
0
18
0
2
Order By: Relevance
“…Whether there is a correlation between clinical outcomes and unmodifiable patient factors such as age and sex in TKA patients remains inconclusive. Some studies reported that older people have worse clinical outcomes [ 15 , 21 ] whereas others reported older people can expect outcomes equivalent to those in younger people (over 80 vs less than 80 years [ 22 ], over 90 vs less than 90 years [ 23 ]). Regarding sex differences, some [ 24 , 25 ] studies reported that men had better outcomes, whereas other studies [ 21 , 26 ] reported better outcomes in women.…”
Section: Discussionmentioning
confidence: 99%
“…Whether there is a correlation between clinical outcomes and unmodifiable patient factors such as age and sex in TKA patients remains inconclusive. Some studies reported that older people have worse clinical outcomes [ 15 , 21 ] whereas others reported older people can expect outcomes equivalent to those in younger people (over 80 vs less than 80 years [ 22 ], over 90 vs less than 90 years [ 23 ]). Regarding sex differences, some [ 24 , 25 ] studies reported that men had better outcomes, whereas other studies [ 21 , 26 ] reported better outcomes in women.…”
Section: Discussionmentioning
confidence: 99%
“…Degenerative conditions such as osteoarthritis are, therefore, becoming increasingly prevalent. A recent study investigating TKA for nonagenarians in Sweden found good outcomes for death and revision rates, as well as patient-reported outcomes compared with other age groups undergoing TKA [ 1 ]. Complications after TKA have been reported at between five out of 20 and 11 out of 15 TKAs [ 2 , 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…Longer-term follow-up including mortality rate is less easily interpreted among this elderly group because these patients have a short life expectancy. Some authors suggest that death rates up to and including one year postoperatively are better indicators of safety among this age group [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The success of TKA for patients aged over 80 years is a matter of controversy, as prior studies have reported inconsistent associations between advanced age and outcomes. Whereas some studies found patient-reported outcomes (PROs) following TKA in older patients to be comparable to those in their younger counterparts, 5 7 others reported them to be significantly inferior in elderly patients. 8 , 9 Furthermore, some studies reported higher complication rates, length of stay (LoS) in hospital, and mortality following TKA in older patients, 6 , 10 12 whilst other studies argued that these outcomes depend more on morbidities and health status, rather than age per se.…”
Section: Introductionmentioning
confidence: 99%